Pelatihan Dasar Psychoacoustic dan Teknik Miking Sound System Masjid untuk Meningkatkan Kompetensi Takmir Masjid Kota Malang - Arif Hidayat; Ainun Nikmah; Lya Rizka Herawati; ST. Ulfawanti Intan Subadra; Sunaryono; Helmi Muhammad; ahmad Taufiq (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
Recently, the use of loudspeakers in mosque activities without rules has been widely complained about by the public, both non-Muslims and Muslims. Improper arrangement of loudspeakers and lack of understanding related to psychoacoustic aspects are the causes of these problems. Therefore, basic psychoacoustic training and mosque sound system miking techniques were held to improve the understanding of mosque administrators in Malang City. The training activities were carried out using lecture and direct discussion methods. The activity, which was attended by 107 participants, received a positive response, where 85% of participants stated that the material presented was clear and easy to understand. Furthermore, almost 70% of participants will also implement sound system miking techniques in the mosques they lead so that the problem of loudspeakers can be resolved. This activity has a positive impact not only on the efficiency of mosque sound system management, but also on the quality of the congregation's worship experience which will indirectly impact the congregation's participation in prospering the mosque.